2018
DOI: 10.1080/09593985.2018.1517198
|View full text |Cite
|
Sign up to set email alerts
|

The effects of type 2 diabetes mellitus and its complications on physical and pulmonary functions: A case–control study

Abstract: Type 2 DM was associated with lower functional capacity and higher rates of comorbid diseases. Therefore, potential causes of these parameters should be considered in the rehabilitation of type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Previous research has been limited to CB assessment of functional capacity in diabetic patients using the 6MWT and other exercise tests [ 3 , 11 , 39 , 40 ]. The 6MWT is a suitable tool for assessing functional capacity in diabetic patients due to its good acceptability and its easy incorporation into daily living activities; thus appearing as the best among the current walking tests [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has been limited to CB assessment of functional capacity in diabetic patients using the 6MWT and other exercise tests [ 3 , 11 , 39 , 40 ]. The 6MWT is a suitable tool for assessing functional capacity in diabetic patients due to its good acceptability and its easy incorporation into daily living activities; thus appearing as the best among the current walking tests [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional capacity is a significant predictor of mortality and morbidity in patients with diabetes mellitus type 2 (DM2) [ 1 ]. Several studies have shown the reduced functional capacity of patients with DM2 compared with the healthy population [ 2 , 3 ]. Although peak oxygen uptake during cardiopulmonary exercise testing is the gold standard for evaluating aerobic functional capacity, it strains the patient’s circulatory system; thus, it is not recommended for patients with DM2 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A DM pode associar-se à distúrbios tanto no metabolismo de carboidratos, quanto no de gorduras e proteínas, alterando a produção de energia utilizada para a realização das atividades diárias, e consequentemente, diminuindo a aptidão cardiorrespiratória (KUZIEMSKI;WOJCIECH;JASSEM, 2019;OKUR et al, 2018;TANGVARASITTICHAI, 2015). Tai et al (TAI et al, 2017), demostrou em seu estudo indivíduos diabéticos apresentam uma redução no volume residual pulmonar, capacidade vital forçada e pico de fluxo expiratório, além de menor pressão expiratória o que indica fraqueza muscular expiratória.…”
Section: Introductionunclassified
“…The lung has been recognized as a target organ in diabetes mellitus as a consequence of alterations secondary to chronic hyperglycemia. The pulmonary complications in diabetes mellitus include a reduction in lung volumes, a decline in carbon monoxide diffusing capacity, decreased elastic lung recoil, and reduced inspiratory muscle strength [2].…”
Section: Introductionmentioning
confidence: 99%